EVALUASI STRATEGI BISNIS DAN PERANCANGAN BALANCED SCORECARD DI PT POINT BREAK INDONESIA - Mochamad Soelton; Anwar Prabu Mangkunegara (Universitas Mercu Buana, 2015)
Business competition is increasingly competitive and today's economic turbulence requires PT. Point Break Indonesia as a company must be able to deal with it. Performance measurement is based only on the financial aspect is felt to be inadequate in assessing the performance of a company. Performance of the company covers a very wide aspect Last decade, the balanced scorecard is one of the most successful concept and design widely used in the discussion of corporate strategy, using the four perspectives in the measurement of financial, customer, internal business processes, and learning and growth. Balanced scorecard can help companies to translate the vision, mission and strategy into action by stimulation utilizing non-financial and financial indicators that are all intertwined in a causal relationship to find a comprehensive corporate performance. Balanced scorecard provides a framework and integrative thinking for management and other stakeholders to control the important changes in the organizational dynamics of competition. Many companies that have used this method and feel quite able to raise his performance, but if it is not sustainable then the development of their business will not be as expected. Keywords : Balanced Scorecard, Business Strategy and Design